DIRECTING ANIMATION DALAM FILM SERI SERIBU SATU CANDI - Prayogo, Koko Is; Sugihartono, Ranang Agung (Capture : Jurnal Seni Media Rekam, 2016)
The making of the work of this final project animation departs from the assumption that the development of Indonesian films is much about the search for identity or an identity, and the struggle of nationalism. However, there are still less of them involving folklore that developed in Indonesian society.By using creative formula of Kentaro Kimura style, the making of this film tries to lift the folklore in Indonesia and try to pack it interestingly. At the stage of idea creation,we do a research of the narrative element of a folklore and reconstructed to explore possibilities in making into a new story.The series of animated films Thousand and One Temple (Seribu Satu Candi) is raised and inspired from the Legend of Prambanan Temple.This film tells the twists and turns of life of Bandung Bondowoso before he becomes a prince of magic. Narratively the concept of comedy makes these stories more interesting.The use of ornamentic concept from batik for the object textures makes this work give more nuances of Nusantara.Keywords :Directing,animation,and Seribu Satu Candi